Efficacy of extracorporeal shock wave therapy and nutraceutical supplementation in the treatment of lateral epicondylitis: a randomized controlled trial - Scaturro, Dalila; Migliorino, Domenico; Tomasello, Sofia; Vecchio, Michele; Moretti, Antimo; Iolascon, Giovanni; Letizia Mauro, Giulia (Frontiers in Rehabilitation Sciences, 2025)
IntroductionNumerous scientific papers have compared different treatment options in the management of lateral epicondylitis. Our study evaluated the efficacy of focal extracorporeal shock wave treatment (ESWT) combined with an integrative nutraceutical treatment of hyaluronic acid, collagen, vitamin C, and manganese, compared with single treatment in patients with lateral epicondylitis in terms of improvement of pain, functional capacity, muscle strength, and reduction of inflammation on ultrasound images.MethodsA single-center, randomized controlled trial (RCT) was conducted in a population of patients with lateral epicondylitis. Patients were enrolled and randomly divided into 3 groups: Group A, consisting of 15 patients who were treated with twenty sessions of therapeutic exercise and five focal ESWT sessions (one session every six days); Group B, consisting of 15 patients who performed twenty sessions of therapeutic exercise and took daily a dietary supplement consisting of Hyaluronic Acid 200 mg, Collagen 5,000 mg, Vitamin C 250 mg and Manganese 10 mg for thirty days; and Group C, consisting of 15 patients, who received a combined treatment of therapeutic exercise, focal ESWT and nutraceutical supplementation The Numerical Rating Scale (NRS) and Patient-Rated Tennis Elbow Evaluation Scale (PRTEE) were administered during the first physiatric examination (T0), at 15 days after the start of treatment (T1), and at a 30-day follow-up (T2). In addition, muscle strength (Handgrip strength) was analyzed by means of a dynamometer, and common extensor tendon thickness (CET Thickness) by ultrasound examination.ResultsData analysis showed that NRS scale scores decreased significantly only in group B at T1 (P < 0.05), and in the three groups at T2 (P < 0.05). Grip strength increased significantly after 30 days only in group C (P < 0.05), while PRTEE scores and CET Thickness decreased significantly at T2 in the three groups (P < 0.05). The comparison among the various groups also showed that the Group C showed statistically significant improvements of function and grip strength at T2, compared with the other groups (P < 0.05).DiscussionOur study demonstrated that the combination of focal ESWT, therapeutic exercise, and nutraceutical supplementation, represent a viable therapeutic option for the management of lateral epicondylitis; likewise, the proposed treatments resulted in a synergistic effect for pain relief and functional recovery in the short term, providing a decrease in the inflammatory state and an increase in muscle strength.